The personal dimension of allied health professional identity: A scoping review in health sciences literature / Die persönliche Dimension der beruflichen Identität von Gesundheitsfachkräften: ein Scoping-Review in der gesundheitswissenschaftlichen Literatur - Belgraver Eline E.W; Coppoolse Remco; Doorn Lia van; Bakker Cok (Sciendo, 2022)
With a shift in healthcare from diagnosis-centered to human- and interprofessional-centered work, allied health professionals (AHPs) may encounter dilemmas in daily work because of discrepancies between values of learned professional protocols and their personal values, the latter being a component of the personal dimension. The personal dimension can be defined as a set of personal components that have a substantial impact on professional identity. In this study, we aim to improve the understanding of the role played by the personal dimension, by answering the following research question: What is known about the personal dimension of the professional identity of AHPs in (allied) health literature?